2017
DOI: 10.1016/j.ijscr.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis with permanent dislocation of the patella treated by total knee arthroplasty through a lateral approach: A report of two cases

Abstract: HighlightsPermanent dislocation of the patella (PDP) is a rare condition. In cases of PDP with tibiofemoral arthritis, total knee arthroplasty may be performed through a medial parapatellar approach with patellar realignment in general.We performed two total knee arthroplasties for PDP with lateral tibiofemoral arthritis through a lateral approach without any realignment procedure.We only have 2 cases, but we suggest that TKA through a lateral approach have potential to be a new treatment option to achieve bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 11 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…However, MPFLR and tibial tubercle osteotomy have been added to most cases, and the degree of lateral release and the methods of exposure and closure remain unknown [7]. Fujiwara et al reported a case similar to ours that could be treated simply with TKA using a lateral approach [8]. However, they only described the closure method as follows: "The gap of the lateral capsule is to be covered by soft tissue such as the infrapatellar fat pad or the lateral meniscus" [8].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, MPFLR and tibial tubercle osteotomy have been added to most cases, and the degree of lateral release and the methods of exposure and closure remain unknown [7]. Fujiwara et al reported a case similar to ours that could be treated simply with TKA using a lateral approach [8]. However, they only described the closure method as follows: "The gap of the lateral capsule is to be covered by soft tissue such as the infrapatellar fat pad or the lateral meniscus" [8].…”
Section: Discussionmentioning
confidence: 66%
“…Fujiwara et al reported a case similar to ours that could be treated simply with TKA using a lateral approach [8]. However, they only described the closure method as follows: "The gap of the lateral capsule is to be covered by soft tissue such as the infrapatellar fat pad or the lateral meniscus" [8].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Some studies reported successful clinical cases of patellar dislocation treated by TKA with vastus medialis advancement [6][7][8][9]. Matsushita et al reported satisfactory outcomes of TKA combined with MPFL reconstruction for patients with chronic patellar dislocation with valgus deformity of 3 Case Reports in Orthopedics the knee [14].…”
Section: Discussionmentioning
confidence: 99%
“…The increased femoral anteversion angle (FAA) has been reported as a risk factor of patellofemoral incongruity and patellar dislocation, because the internal torsion on the distal femur lateralizes the patellar joint and persistent force leads to increased pressure on the PF joint [3,4]. Recently, there have been reports of patellar dislocation with PF osteoarthritis treated by total knee arthroplasty (TKA) [5][6][7][8][9]. However, it is controversial to perform TKA on a knee without tibiofemoral (TF) joint OA.…”
Section: Introductionmentioning
confidence: 99%